Evaluasi Pengelolaan Program Praktik Kerja Lapangan (PKL) Kelas XI SMK Bidang Keahlian Bisnis dan Manajemen - Neliwati Neliwati; Khairani Khairani; Sonia Purba Tambak (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Field Work Practices (PKL) are learning opportunities for SMK/MAK, SMALB, and LKP students that are carried out through work practices in the workplace within a predetermined amount of time in accordance with the curriculum and workplace requirements. Since the school is in charge of running the field work practice program, it is necessary to conduct research by evaluating how the program is run. This study aims to reveal and analyze a number of things in detail, including (1) locating and evaluating a strategy. 2) comprehending and evaluating activity program control. Document review, observation, and interviews are used in this study's evaluative methodology. This study was carried out at Private Vocational School Al Washliyah 9 Perbaungan, Serdang Bedagai Regency, North Sumatra Province. The school possesses expertise in business and management as well as two expertise competencies, which are Automation of Office Governance and Institutional Financial Accounting. The CIPP evaluation model, which evaluates Contex (C), Input (I), Process (P), and Product (P), is the one that is utilized. In order to produce an interpretive assessment, the CIPP model was modified in accordance with the requirements of the evaluation. At Al Washliyah 9 Private Vocational School, field work practices were planned and managed in accordance with effectiveness standards, including the Good program standards. Additionally, the evaluation results must be enhanced to become a very high standard for achieving the desired outcomes. Keywords: management, Practical Field, Vocational High School